Minimally Invasive Advance Beautification Rhinoplasty - Alam, Dr Munir (International Journal of Innovative Research in Medical Science, 2019)
Background: Rhinoplasty is the most challenging surgical procedure amongst all the aesthetic/cosmetic operations. As for the challenges with rhinoplasty are great, so the need of minimal invasive techniques, less scarring, quick recovery especially in the asian nose with thick sebaceous nasal tip skin. The aim in beautification rhinoplasty is to improve the aesthetic proportions, volumes, and angles of the nose, adapted to the face as a whole. Frequently the patient desire is to achieve symmetrical, smaller, more attractive nose with better respiration, which require the identification of aesthetic and functional problems to execute the planned operation. Study Period: The author have had performed fifty seven rhinoplasty procedures from July 2014 to July 2017 with almost 6 months follow up period. Material and Methods: The techniques used for almost all rhinoplasty procedures includes T-excision, humpectomy, macidonian technique for lateral digital osteotomy, columellar sliding and nasal tip refinement. Where needed combined with septoplasty, turbinectomy, polypectomy etc additional procedure in nine patients out of fifity seven. Serdev Sutures® in rhinoplasty include: tip rotation, refinement / narrowing of the tip, lower and medial thirds, alar base narrowing and nasal dorsum lifting of concavities and irregularities. Results: With the advancement in minimal invasive techniques, it has become possible to achieve excellent satisfactory results (80 -100 % by using visual analogue scoring system), where indicated combined with ENT Surgery. Conclusion: The correct nose proportions, angles, and volumes guides the appropriate procedure to the surgeon. By using advance minimal invasive techniques provide predictable results for close rhinoplasty, nearly normal “nonoperated appearance” after atraumatic mini-invasive surgery.